STRATEGI GURU DALAM MEMBENTUK KARAKTER PEDULI LINGKUNGAN PADA PESERTA DIDIK DI SDN 09 SUNGAI KELAMBU KECAMATAN TEBAS TAHUN PELAJARAN 2023-2024 - Melia Melia; Mujahidin, Saripah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The aim of this research is to reveal about, 1) to find out the strategies implemented by teachers in forming environmentally caring character in students at SDN 09 Sungai Kelambu, Tebas District, 2023-2024 academic year. 2) find out the implications of forming an environmentally caring character in students at SDN 09 Sungai Kelambu, Tebas District, 2023-2024 academic year. 3) knowing the supporting and inhibiting factors in forming an environmentally caring character in students at SDN 09 Sungai Kelambu, Tebas District, 2023-2024 academic year. This research uses descriptive research with a qualitative approach, data collection techniques using interviews, documentation, observation. The data analysis techniques used are data reducation, data presentation, and drawing conclusions. Data validity checking triangulation and member checks. The results of this research show that; 1) the strategy implemented by teachers in forming environmentally caring character in students is a school program tehat has been ambedded in students both within the scope of the school environments and outside the school. 2) The implications of forming an environmentally caring character in students are environmental awareness and higher responsibility in students, a growing sense of enthusiasm and pride in students, as well as students’ appearance and personality that reflects an environmentally caring character. 3) supporting and inhibiting factors in forming an environmentally caring character in students, limitations in equipment that are not yet fully equipped, as well as students’ awareness and responsibility that in unstable and undisciplined